The occurence of trichloroacetic acid (tcaa): indications of a natural production? - Haiber, Georg; Jacob, G.; Niedan, Volker Wolfgang; Nkusi, Gérard; Schöler, Heinz Friedrich (Chemosphere, 1996)
TCAA was identified in the nanogram range in several environmental compartments including bog water, glacier ice, snow, rain, spring water and in soil lysimeters. Some of these results indicate a naturally induced formation of TCAA. In addition different short chained aliphatic acids (acetic acid, malic acic, lactic acid, fumaric acid, malonic acid, citric acid, acetonedicarboxylic acid), which are involved in soil processes were incubated with the chlorinating enzyme chloroperoxidase (CPO) from the fungus Caldariomyces fumago and converted in the presence of sodium chloride and hydrogenperoxide. Trichloroacetic acid (TCAA) was formed in all reactions in concentrations ranging from some promille to 8% in regard of the applied enzyme.